In-service education problems of science teachers in the public secondary schools in Quezon City - Sirisab, Sununta 1946- (1974)
This study is an analysis of the problems on in-service education besetting science teachers in public elementary schools in Quezon City.
Thesis (M.Ed.)--University of the Philippines System
Keywords: Science teachers -- Quezon City; Teachers -- In-service training -- Philippines